2013
DOI: 10.1111/cen.12033
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and long‐term follow‐up outcomes of testicular adrenal rest tumours in children and adolescent males with congenital adrenal hyperplasia

Abstract: Objective There are a few studies regarding the prevalence of testicular adrenal rest tumours (TARTs) in boys and adolescent males with congenital adrenal hyperplasia (CAH), and there is little information regarding the treatment outcomes in patients with TARTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
20

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 29 publications
5
56
0
20
Order By: Relevance
“…Two case series and one case report describe patients with 11βOHD and TARTs [144][145][146]. One of these series was a follow-up study of 60 boys and adolescent males with CAH of which five had 11βOHD.…”
Section: Testicular Adrenal Rest Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two case series and one case report describe patients with 11βOHD and TARTs [144][145][146]. One of these series was a follow-up study of 60 boys and adolescent males with CAH of which five had 11βOHD.…”
Section: Testicular Adrenal Rest Tumorsmentioning
confidence: 99%
“…One of these series was a follow-up study of 60 boys and adolescent males with CAH of which five had 11βOHD. Three of five boys (60%) were identified to have TART based on ultrasonography [145]. All three cases had poor biochemical control and were diagnosed with TARTs at ages 14, 16 and 17 years.…”
Section: Testicular Adrenal Rest Tumorsmentioning
confidence: 99%
“…CYP21A2, CYP11B1 and NR0B1/DAX1 mutations), the malignancy risk for the testis is estimated as being low (37,38,39). 46,XY patients with 21-hydroxylase deficiency and 11b-hydroxylase deficiency may develop TARTs, which can compromise fertility and sometimes be mistaken for Leydig cell malignancy; but TARTs are benign (37,40) and can be controlled by proper treatment (41). Importantly, testosterone overproduction as seen in some of these defects seems not to be associated with increased germ cell cancer risk (15,37).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…However, if high gonadotropin levels are found, they can be indicative of a testicular failure (22,30). Whereas some investigators found that TARTs regressed and spermatogenesis was reactivated when glucocorticoid therapy was instituted or intensified (11,31), others report that patients remain azoospermic (27,32). The use of dexamethasone (0.25-0.5 mg p.o.…”
Section: Hormonal Treatment and Outcomementioning
confidence: 99%